High Mortality among 30-Day Readmission after Stroke: Predictors and Etiologies of Readmission - Nouh, Amre M.; McCormick, Lauren; Modak, Janhavi; Fortunato, Gilbert; Staff, Ilene (Frontiers in Neurology, 2017)
Background: Although some risk factors for readmission have been reported, the mortality risk is unclear. We sought to evaluate etiologies and predictors of 30-day readmissions and determine the associated mortality risk. Methods: This is a retrospective case-control study evaluating 1544 patients admitted for stroke (hemorrhagic, ischemic or TIA) from January 2013-December 2014. Of these, 134 patients re-admitted within 30 days were identified as cases;1418 other patients, with no readmissions were identified as controls. Patients readmitted for hospice or elective surgery were excluded. An additional 248 patients deceased on index admission were included for only a comparison of mortality rates. Factors explored included socio-demographic characteristics, clinical comorbidities, stroke characteristics, and length of stay. Chi-square test of proportions and multivariable logistic regression were used to identify independent predictors of 30-day stroke readmissions. Results: Among the 1544 patients, 67% of index stroke admissions were ischemic, 22% hemorrhagic, and 11% TIA. The 30-day readmission rate was 8.7%. The most common etiologies for readmission were infection (30%), recurrent stroke and TIA (20%), and cardiac complications (14%). Significantly higher proportion of strokes and TIA presented within the first week (p=0 .039) and had a shorter index admission length of stay (p=0.027). Risk factors for 30-day readmission included age > 75 (p=0.02), living in a facility prior to index stroke (p=0.01), history of prior stroke (p=0.03), diabetes (p=0.03), chronic heart failure (p=<0.001), atrial fibrillation (p=0.03), index admission to non-neurology service (p<0 .01), and discharge to other than home (p<0.01). On multivariate analysis, index admission to a non-neurology service was an independent predictor of 30-day readmission (p=<0.01). The mortality after a 30-day readmission was higher than index admission (36.6% vs. 13.8% p =<0.001) (OR 3.6 95%CI 2.5-5.3) and highest with recurrent stroke (p=0.006). Conclusion: Approximately one-third of 30-day readmissions were infection related and one fifth returned with recurrent stroke or TIA. Index admission to non-neurology service was an independent readmission risk factor.The mortality rate for 30-day readmission after stroke is more than 2.5 times greater than index admissions. Identifying high risk patients, appropriate level of service and early outpatient follow-up may help reduce 30-day readmission and associated mortality